Over-expression of AhR (aryl hydrocarbon receptor) induces neural differentiation of Neuro2a cells: neurotoxicology study - Ishihara-Sugano Mitsuko; Yoshimura Seiko; Akahoshi Eiichi (BMC, 2006)
Abstract Background Dioxins and related compounds are suspected of causing neurological disruption in human and experimental animal offspring following perinatal exposure during development and growth. The molecular mechanism(s) of the actions in the brain, however, have not been fully investigated. A major participant in the process of the dioxin-toxicity is the dioxin receptor, namely the aryl hydrocarbon receptor (AhR). AhR regulates the transcription of diverse genes through binding to the xenobiotic-responsive element (XRE). Since the AhR has also been detected in various regions of the brain, the AhR may play a key role in the developmental neurotoxicity of dioxins. This study focused on the effect of AhR activation in the developing neuron. Methods The influence of the AhR on the developing neuron was assessed using the Neuro2a-AhR transfectant. The undifferentiated murine neuroblastoma Neuro2a cell line (ATCC) was stably transfected with AhR cDNA and the established cell line was named N2a-Rα. The activation of exogenous AhR in N2a-Rα cells was confirmed using RNAi, with si-AhR suppressing the expression of exogenous AhR. The neurological properties of N2a-Rα based on AhR activation were evaluated by immunohistochemical analysis of cytoskeletal molecules and by RT-PCR analysis of mRNA expression of neurotransmitter-production related molecules, such as tyrosine hydroxylase (TH). Results N2a-Rα cells exhibited constant activation of the exogenous AhR. CYP1A1, a typical XRE-regulated gene, mRNA was induced without the application of ligand to the culture medium. N2a-Rα cells exhibited two significant functional features. Morphologically, N2a-Rα cells bore spontaneous neurites exhibiting axon-like properties with the localization of NF-H. In addition, cdc42 expression was increased in comparison to the control cell line. The other is the catecholaminergic neuron-like property. N2a-Rα cells expressed tyrosine hydroxylase (TH) mRNA as a functional marker of catecholaminergic neurotransmitter production. Thus, exogenous AhR induced catecholaminergic differentiation in N2a-Rα cells. Conclusion The excessive activation of AhR resulted in neural differentiation of Neuro2a cells. This result revealed that dioxins may affect the nervous system through the AhR-signaling pathway. Activated AhR may disrupt the strictly regulated brain formation with irregular differentiation occurring rather than cell death.